IMPLIKASI PENERAPAN PERATURAN MAHKAMAH AGUNG NO. 1 TAHUN 2016 TENTANG PROSEDUR MEDIASI DI PENGADILAN TERHADAP CAPAIAN ASAS FLEKSIBILITAS (Studi Kasus pada Pengadilan Agama Kelas 1 B Watampone) - Jamaluddin, Jamaluddin (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2017)
One of the civil event principles of justice is flexibility ground as contained in Section 2 ( 4) Law Number 48 the Year 2009 about Judicial Power that jurisdiction conducted mainly, quickly, and light expense. Tone with Perma RI Number considering 1 the Year 2016 about the procedure of mediation in Justice. Base Flexibility represents expectation all party, especially to is drawee of divorce dispute in Justice Of Religion. PERMA Number 1 the Year 2016 representing Appellate Court effort in integrating meditation into process attend legal procedure in Justice, where expected can overcome the problem of heaping of the case, and also strengthen and maximize function institute justice in solving of dispute. Besides that, process mediation becomes to increase because there are section 130 HIR and 154 RBG obliging mediation each early conference, and if not be executed to cause conference of cancelation for the shake of law. Even farther that mediation can be executed till the decision of Eintracht. But that way direct exes of the PERMA is its time become length (old), expense increase, and entangle mediator with all is the protocol of him so that make process attends legal procedure do not modestly (complicated). This Research represent research of field (Field of Research) having the character of qualitative [in] area punish by using the approach of juridic, that is using science theory punish in explaining implication applying of Regulation of Appellate Court of RI to flexibility ground performance at dispute divorce in Justice of Religion Class 1 B Watampone.